REGIONAL INTEGRATION AND GLOBALIZATION - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Regional integration has been defined as an association of states based upon location in a given geographical area, for the safeguarding or promotion of the participants, an association whose terms are fixed by a treaty or other arrangements.Philippe De Lombaerde and Luk Van Lange hove define regional integration as a worldwide phenomenon of territorial systems that increases the interactions between their components and creates new forms of organization, co-existing with traditional forms of state-led organization at the national level.According to Hans van Ginkel, regional integration refers to the process by which states within a particular region increase their level of interaction with regard to economic, security, political, and also social and cultural issues.In short, regional integration is the joining of individual states within a region into a larger whole. The degree of integration depends upon the willingness and commitment of independent sovereign states to share their sovereignty.